SUMOylation of VEGFR2 regulates its intracellular trafficking and pathological angiogenesis - Huanjiao Jenny Zhou (Nature Portfolio, 2018)
VEGFR2 is a central regulator of angiogenesis. Here Zhou et al. report that SUMOylation of VEGFR2 regulates its subcellular localisation and activity, and that endothelial-specific knockout of the SUMO endopeptidase SENP1 protects against VEGFR2-mediated pathological angiogenesis.